The role of homeobox gene NKX3.1 in prostate cancer - Patel, R (2014)
NKX3.1, a prostate specific homeobox gene is a known marker of prostate epithelium during embryogenesis and is also expressed subsequently through different stages of prostate differentiation. However, all studies on NKX3.1 are focused on its regulation by androgen receptor (AR). The aim of this project is to establish the role of NKX3.1 in differentiation in prostate cancer, independent of AR regulation. In this thesis, I characterize the cell lines in terms of their differentiation capabilities in 3D, expression levels of NKX3.1 and the mismatch repair status. The genes potentially involved in differentiation and regulators of NKX3.1 are also identified using microarray data of the cell lines (Chapter 3). Although NKX3.1 plays a key role in prostate development no studies have been conducted on the effect of NKX3.1 expression on differentiation capabilities of prostate cell lines. In Chapter 4, this was investigated by siRNA mediated knockdown of NKX3.1 in 22Rv1 cell line and overexpression of NKX3.1 in PC3 (designated PC3-Nkx3.1) and PNT1a cells followed by growth in 3D. These functional studies show that the expression of NKX3.1 is vital for lumen formation in 3D, which is used as a measure of differentiation. The microarray data and overexpression of NKX3.1 studies suggest that this gene may also be involved in inhibiting epithelial to mesenchymal transition (EMT). Homeobox B13 (HOXB13) was identified as one of the downstream targets of NKX3.1. NKX3.1 and HOXB13 expression levels are positively correlated not only in the panel of prostate cell lines but also in the NKX3.1 overexpression and knockdown studies (Chapter 5). The results of the work presented in this thesis demonstrate that there is a striking parallel between the function of NKX3.1 in prostate and Caudal-type homeobox 1 (CDX1) in the colon and rectum. In conclusion, NKX3.1 plays a key role as a tumour suppressor in prostate cancer by controlling differentiation of prostate cancer cells.